‘What will the lawyers say?’: Australian newsroom perspectives on journalism ethics and naming criminal suspects in a digital world - Lillebuen, Steve; Lidberg, Johan (My University, 2024)
This article examines journalism ethics and identifying criminal suspects in Australian news coverage. This study builds off our previous research, which established that naming is so commonplace, it is occurring on a daily basis in the state of Victoria, even in cases with little public interest justification. A survey of 410 Australian news media professionals, as well as twelve semi-structured interviews, found journalists believe naming is an ethical decision, but it is not high on their agenda with naming treated as their default position. Media lawyers play a key role in newsroom naming practices with the legal strongly influencing what is deemed ethical. These findings are significant because it is the first empirical data from Australia and the findings are in stark contrast with news reporting practices in other countries. This article argues for stronger ethical guidelines in a digital news media environment where naming is now global and forever.
Keywords: news media; journalism; naming practices; ethics; crime coverage